Political connections and firm performance: Evidence from Indonesia - Muhammad Rizky, P. S.; Mohd Thas Thaker, Hassanudin *; Ahmad, K. (Universiti Putra Malaysia, 2020)
We study the performance of Indonesian firms based on political and non-political connections for the period of 2007 to 2018. Using advanced econometrics approach, we provide a comparative empirical analysis of the linkages between performance, firmspecific characteristics, and macroeconomic variables for politically-connected (PC) and non-politically-connected (NPC) firms. In addition, we also offer an empirical analysis of performance determinants across industries categories and Shariah-compliance status. The results show the performance (measured by ROA and ROE) of PC and NPC are significantly influenced by firm-specific characteristics (leverage, tangibility, firm size, and liquidity). While, only one macroeconomic factor (economic growth) has significant effect to ROA, and two macroeconomic factors (economic growth and inflation) have significant effect to ROE of PC firms. Focusing on politically-connected firms, we find a variation of performance determinants (both firm-specific and macroeconomic factors) across different industries categories. Interesting insight we noted that there is a persistent negative effect of tangibility on performance indicators in agriculture-, chemicals-, consumer goods-, infrastructure-, mining-, and miscellaneous industries. In terms of Shariah-compliant status, tangibility also exerts the negative and significant effect on ROA of both Shariahcompliance and non-Shariah compliance status. Another important insight is that the Shariah non-compliance status allows the politically-connected firms to use more leverage as there is no Shariah restrictions imposed to them. This suggests that high leverage significantly contributes to increase the ROA of Shariah non-compliance firms. Therefore, political linked status is still an imperative factor in influencing the Indonesian firm’s performance. This finding lends some support to the argument on the political connection and the performance of firm and offers several policy implications from a practical point of view with regard to the subject matter.